A systematic review of interventions to retain chronically ill occupationally active employees in work: can findings be transferred to cancer survivors?. (4th May 2019) - Stapelfeldt, Christina Malmose; Klaver, Kete Mechteld; Rosbjerg, Rikke Smedegaard; Dalton, Sanne Oksbjerg; Bültmann, Ute; Labriola, Merete; Duijts, Saskia Francisca Anthony
Abstract: Background: Interventions supporting occupationally active cancer survivors to retain work and prevent adverse work outcomes, beyond return to work, are scarce. As lessons may be learned from interventions that have been evaluated in working employees with other chronic diseases than cancer, the objective of this review was to summarize the characteristics of these interventions. Material and methods: Studies were identified through computerized PubMed, EMBASE and PsycINFO searches, without any language or year of publication restrictions. Randomized controlled trials were included if they evaluated the effectiveness of interventions to retain chronically ill occupationally active employees in work. Two authors independently extracted data from each study and assessed the risk of bias. Results: The search identified 536 unique studies, of which 18 met the inclusion criteria. All included studies had a low risk of bias. (Psycho-)educational interventions for chronically ill employees to retain work were evaluated in two studies, physical interventions in three studies, vocational/work-related interventions in five studies, and multidisciplinary interventions in eight studies. Vocational/work-related and multidisciplinary interventions, and the involvement of professional trainers, showed the most promising effects in retaining employees. However, small sample sizes may have caused imprecise effect estimates. Conclusion: Based on studies focusing on occupationally active employees with other chronic diseases than cancer, it is advised that working cancer survivors should be offered tailored interventions, by skilled trainers, to sustain their employability. Shared goal setting, with relevant stakeholders, and vocational components should be included, potentially as part of a multidisciplinary intervention.